Impactos da Reforma Trabalhista na ação do Sindicato dos Metalúrgicos de Joinville - Nascimento, Ana Paula (2020)
The general theme of this dissertation is the impact of the Labor Reform and the mechanisms of action articulated by Sindicato dos Metalúrgicos de Joinville. We analyzed the trade unions historical trajectory, highlighting the influences and links created with other trade unions in the city, with the Central Única dos Trabalhadores and the Partido dos Trabalhadores. We discussed the confrontations made by the Union during the decades of 2000 and 2010 until the enactment of the Labor Reform in 2017. The Labor Reform changed the Brazilian trade unionism, with regard to the representation, organization and financial support of the unions. In this dissertation, supported by economic data from the metallurgical category of Joinville, analysis of the bibliography, interviews, analysis of promotional materials, collective work agreements and comparisons with other Brazilian metallurgical trade unions , we analyzed the Union's responses to resist the Reformation, especially economic and political actions. The results show that the Union has challenged the Reform and sought to adapt to the new imposed context, promoting unionization campaigns and closer ties with the metallurgical base. In order to maintain its survival, the Joinville Metalworkers Union has sought to attract its base by offering assistance services, through agreements. Negotiations have focused both on curbing employers' advances and guaranteeing the rights negotiated in previous collective agreements.